Bacillus subtilis vector based oral rabies vaccines induced potent immune response and protective efficacy in mice - Zhang, Ying; Mo, Ruo; Sun, Sheng; Cui, Zhanding; Liang, Bo; Li, Entao; Wang, Tiecheng; Feng, Ye; Yang, Songtao; Yan, Feihu; Zhao, Yongkun; Xia, Xianzhu (Frontiers in Microbiology, 2023)
Rabies is a worldwide epidemic that poses a serious threat to global public health. At present, rabies in domestic dogs, cats, and some pets can be effectively prevented and controlled by intramuscular injection of rabies vaccine. But for some inaccessible animals, especially stray dogs, and wild animals, it is difficult to prevent with intramuscular injection. Therefore, it is necessary to develop a safe and effective oral rabies vaccine. In this study, we constructed recombinant Bacillus subtilis (B. subtilis) expressing two different strains of rabies virus G protein, named CotG-E-G and CotG-C-G, immunogenicity was studied in mice. The results showed that CotG-E-G and CotG-C-G could significantly increase the specific SIgA titers in feces, serum IgG titers, and neutralizing antibodies. ELISpot experiments showed that CotG-E-G and CotG-C-G could also induce Th1 and Th2 to mediate the secretion of immune-related IFN-γ and IL-4. Collectively, our results suggested that recombinant B. subtilis CotG-E-G and CotG-C-G have excellent immunogenicity and are expected to be novel oral vaccine candidates for the prevention and control of wild animal rabies.